CLINICAL AND RADIOGRAPHIC EVALUATION OF BIOMATERIALS USED IN DIFFERENT ENDODONTIC PROCEDURES-CASE SERIES - Sera Şimşek Derelioğlu; Periş Çelikel; Aybike Baş (Ankara University, 2022)
Introduction: Endodontic treatment may be required for the permanent teeth due to different reasons in childhood. Biological materials such as MTA and Biodentine® have started to be used nowadays in different endodontic treatment. Studies have shown that these materials stimulated the formation of new vascularized tissue in the apical of mature teeth with necrotic pulp and with periapical lesions. In addition, MTA and Biodentine® are preferred in direct and indirect pulp capping due to their properties such as biocompatibility and impermeability. Purpose: The aim of this study is to examine the teeth clinically and radiologically after the use of Biodentine® and MTA as a barrier on the pulp capping, Cvek pulpotomy and regenerative endodontic treatment. Case Series: Case 1: A 12-year-old girl presented at our clinic with complaints of intermittent pain and cold sensitivity in her tooth #16. Direct pulp capping was performed with MTA. Case 2: An 7-year-old boy with a trauma associated complicated crown fracture in his tooth #11 was admitted to our clinic. Cvek pulpotomy was performed with Biodentine®. Case 3: An 8-year-old girl with trauma associated crown fracture in her tooth #11 was admitted to our clinic. Regenerative endodontic treatment was applied with Biodentine®. Case 4: Indirect pulp capping was performed with MTA to a 7-year-old boy admitted to our clinic with the complaint of cold sensitivity in his tooth # 46. Conclusion: Today, the success rate is high in vital pulp treatments with newly developed materials such as MTA and Biodentine®. In addition, root development continues after regenerative endodontic treatments with Mineral Trioxide Aggregate (MTA) or Biodentine® in non-vital and open-apex teeth.